Aspek Perlindungan Hukum dalam Praktik Pengalihan Kredit Pemilikan Rumah Melalui Perjanjian di Bawah Tangan - Hendra; Irwan (Amicus Curiae: Journal of Law and Justice Dialogue, 2025)
The practice of transferring a Home Ownership Loan (KPR) through underhand agreements is still common in society, especially when the debtor is no longer able to continue their credit obligations. This transfer is generally carried out without the approval of the bank as the creditor and without involving authorized officials, thus giving rise to legal issues related to legal certainty and protection for the buyer. This article aims to examine the legal protection of the practice of transferring a KPR through underhand agreements and examine the legal principles that can serve as a basis for protection for parties acting in good faith. The research method used is normative juridical legal research with a statutory and conceptual approach, through a review of primary, secondary, and tertiary legal materials. The results of the study indicate that underhand KPR transfers do not provide optimal legal certainty because they do not comply with formal banking and land law procedures. However, from a civil perspective, such agreements can still be considered valid as long as they meet the requirements for a valid agreement and are carried out in good faith. Legal protection for buyers can be obtained through the application of the principle of good faith, consumer protection, and dispute resolution mechanisms through the courts.